2017
DOI: 10.1021/acsnano.7b05020
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Bimetallic Phosphide/Sulfide Nanocomposite for Efficient Solar-Energy-Driven Overall Water Splitting

Abstract: Solar-driven overall water splitting is highly desirable for hydrogen generation with sustainable energy sources, which need efficient, earth-abundant, robust, and bifunctional electrocatalysts for both oxygen evolution reaction (OER) and hydrogen evolution reaction (HER). Herein, we propose a heterogeneous bimetallic phosphide/sulfide nanocomposite electrocatalyst of NiFeSP on nickel foam (NiFeSP/NF), which shows superior electrocatalytic activity of low overpotentials of 91 mV at -10 mA cm for HER and of 240… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(127 citation statements)
references
References 76 publications
3
124
0
Order By: Relevance
“…The CoP-Co 2 P@ PC/PG||CoP-Co 2 P@PC/PG device (Figure 5A) only requires a cell voltage of 1.567 V to drive the OWS to reach a current density of 10 mA cm −2 , superior to Pt/C||IrO 2 pair (1.576 V) and their pure-phase counterparts based devices ( Figure S21, Supporting Information). Also, the OWS activity of CoP-Co 2 P@PC/PG NHs is better than other reported bifunctional catalysts, such as Cu 0.3 Co 2.7 P/NC (1.620 V for 10 mA cm −2 ), [15] FeCoP nanosheets (1.600 V for 10 mA cm −2 ), [22] NiFeSP/NF (1.580 V for 10 mA cm −2 ), [32] Ni 1−x Fe x PS 3 @MXene (1.650 V for 10 mA cm −2 ), [33] NiCo 2 S 4 NW/NF(1.630 V for 10 mA cm −2 ), [34] and so on. The detailed comparison of OWS activity of CoP-Co 2 P@PC/PG NHs with other reported catalysts is provided in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 76%
“…The CoP-Co 2 P@ PC/PG||CoP-Co 2 P@PC/PG device (Figure 5A) only requires a cell voltage of 1.567 V to drive the OWS to reach a current density of 10 mA cm −2 , superior to Pt/C||IrO 2 pair (1.576 V) and their pure-phase counterparts based devices ( Figure S21, Supporting Information). Also, the OWS activity of CoP-Co 2 P@PC/PG NHs is better than other reported bifunctional catalysts, such as Cu 0.3 Co 2.7 P/NC (1.620 V for 10 mA cm −2 ), [15] FeCoP nanosheets (1.600 V for 10 mA cm −2 ), [22] NiFeSP/NF (1.580 V for 10 mA cm −2 ), [32] Ni 1−x Fe x PS 3 @MXene (1.650 V for 10 mA cm −2 ), [33] NiCo 2 S 4 NW/NF(1.630 V for 10 mA cm −2 ), [34] and so on. The detailed comparison of OWS activity of CoP-Co 2 P@PC/PG NHs with other reported catalysts is provided in Table S3 (Supporting Information).…”
Section: Resultsmentioning
confidence: 76%
“…In this regard, Zhang and co-workers used the hexagonal NiS (0001) as the pristine model and investigated the effect of dual doping Fe and P on their electronic structure via DFT calculations. [98] As demonstrated in Figure 5a, the replacement of one topmost surface Ni/S atom by Fe and P atoms could generate the NiFeS (Figure 5a Figure 5a-a5, a6), respectively. The results revealed that the P atom preferred to be doped on the inner layer sites while the Fe doping would cause segregation of the inner P to the surface.…”
Section: Anions and Cations Dual Dopingmentioning
confidence: 98%
“…In common, the cations and anions dual‐doping can engender dual synergetic effects on modulating adsorption energy, electrical conductivity, etc. In this regard, Zhang and co‐workers used the hexagonal NiS (0001) as the pristine model and investigated the effect of dual doping Fe and P on their electronic structure via DFT calculations . As demonstrated in Figure 5 a, the replacement of one topmost surface Ni/S atom by Fe and P atoms could generate the NiFeS (Figure a‐a3) and NiSP (Figure a‐a4), and NiFeSP (Figure a‐a5, a6), respectively.…”
Section: Modulated Strategies For Tmps In Electrocatalytic Her Oer mentioning
confidence: 99%
See 2 more Smart Citations